COMMUNICATION MANAGEMENT FOR PROMOTING ECOTOURISM IN KANCHANABURI PROVINCE BAN E TONG COMMUNITY - Saewong, Sittichai; Kumsubha, Bhanond; Watcharasarnsab, Taksaya; Eietagoon, Wirot (Journal of MCU Nakhondhat, 2024)
This study aims to examine the communication network, as well as communication and public relations strategies to promote ecotourism in Ban E-Tong Community, Kanchanaburi Province, using a quantitative approach by interviewing in-depth with 13 members of the community leadership, entrepreneurs, and relevant parties to the community ecotourism, and eight tourists to the community, along with content analysis. The study found that the communication network to promote ecotourism in Ban E-Tong Community was organized as follows: 1) The role and duties of the community members was found to be clearly allocated, with the government officials having a major role in community ecological tourism; 2) There were two community communication types 2.1) Formal and 2.2) Informal 3) Regarding the ecotourism promotion management, this study found that the community had public relations and mutual understanding planning, in addition to creating community participation. Furthermore, regarding the study of communication and public relations strategies to promote ecotourism in the community, focusing on management of community communication to the target group, the strategies could be divided into three parts: 1) Direction setting, which was found that the community set the direction on the pricing of products and services in the community, and the community’s online channels were mainly used 2) Regarding the content and channel of the community’s communication, it was found that community Facebook group were used to communicate with the tourists 3) Regarding the participatory behavior of the tourists in the community, it was found that tourists shared community information and visited from the Facebook group more than from the entrepreneurs’ media channels.